Knowledge, attitudes, and referral practices regarding animal bites and prevention of human rabies among Traditional Health Practitioners in the eThekwini District in KwaZulu-Natal Province, South Africa, 2022 - Mabona, Maxwell; Zwane, Thembekile; Mhlongo, Babongile; Kuonza, Lazarus; Phafane, Poncho (Frontiers in Tropical Diseases, 2025)
BackgroundSouth Africa experiences approximately 10 human rabies deaths annually, despite the availability of effective post-exposure prophylaxis (PEP). In KwaZulu-Natal Province, one of the most rabies-affected provinces, many animal bite patients initially seek help from Traditional Health Practitioners (THPs) before considering conventional healthcare facilities. Prompt referral of animal bite patients for PEP initiation by THPs can be lifesaving. Our study aimed to assess the knowledge, attitudes, and referral practices regarding human rabies and the associated factors among THPs in eThekwini District, KwaZulu-Natal.MethodsA cross-sectional study was conducted among registered THPs in eThekwini District, collecting data through a structured, standardized questionnaire. The questionnaire was administered through physical and telephone interviews. We described socio-demographic characteristics using summary statistics. Multivariable logistic regression was used to analyze factors associated with knowledge, attitudes, and referral practices. Odds ratios (OR) were used with 95% confidence intervals, and a probability (p)-value of ≤0.05 was considered statistically significant.ResultsThe study involved 204 THPs, with 74% (150/204) being female. The median age was 43 years (inter-quartile range: 22–75 years) and 31% (64/204) had over 10 years of practicing experience. The majority of THPs had inadequate knowledge (80%, 163/204), and poor referral practices (73%, 149/204). However, 91% (186/204) had positive attitudes toward human rabies prevention. Having more experience was associated with adequate knowledge (p<0.01), and positive attitudes (p=0.02). THPs who had adequate knowledge (aOR:2.30 95% CI: 1.12-4.75) and positive attitudes (aOR:1.21 95% CI: 0.37-3.89), had higher odds of having good referral practices.ConclusionDespite THPs in the eThekwini District having positive attitudes towards rabies prevention, gaps exist in their knowledge and referral practices. The study highlights that improving their knowledge and attitudes might lead to better referral practices of animal bite patients for PEP initiation. A multidisciplinary approach that includes THPs is recommended to decrease human rabies deaths in eThekwini District and KwaZulu-Natal Province.